Behavioral Changes During Development of Chronic Kidney Disease in Rats - Renczés, Emese; Marônek, Martin; Gaál Kovalčíková, Alexandra; Vavrincová-Yaghi, Diana; Tóthová, L'ubomíra; Hodosy, Július (Frontiers in Medicine, 2020)
Decreased renal function due to chronic kidney disease (CKD) is associated with anxiety and cognitive decline. Although these mental disorders are often obvious in late stage renal disease patients, they might be unnoticeable or are neglected in early stages of the CKD development. Associations between renal and cognitive dysfunction have been indicated by studies performed mainly in patients undergoing dialysis, which itself represents a stress and decreased quality of life. However, experimental and causal studies are scarce. Our aim was to investigate dynamic changes in behavioral traits during the progression of CKD in an animal model. Thirty 12-week old male rats were used in this experiment. CKD was induced by a subtotal (5/6) nephrectomy. Two, four and six months after surgical induction of CKD, the open field, the light-dark box and the novel object recognition tests were conducted to assess the locomotor activity, anxiety-like behavior and the memory function of rats. Blood urea nitrogen (BUN), plasma concentration of creatinine (CREAT), albumin to creatinine ratio in urine (ACR) along with the renal histology were assessed to monitor the development and severity of CKD. In comparison to control rats, 5/6 nephrectomized rats had significant by 46-66% higher concentration of BUN during the whole follow-up period, as well as by 52% and by 167% higher CREAT and ACR, respectively six months after surgery. Although the effect of time was observed in some behavioral parameters, nephrectomy did not significantly influence either locomotor activity, or anxiety-like behavior, or memory function of animals. Two and four months after surgery, animals moved shorter distance and spent less time in the center zone. However, the open-field ambulation returned back to the baseline level six months after CKD induction. Although nephrectomized rats displayed impaired kidney function as early as two months after surgery, no significant differences were found between the CKD and the control rats in any of the observed behaviors. Further studies are needed in order to evaluate whether behavioral abnormalities are related to severity of CKD or might be attributed to psychosocial aspect of end-stage renal disease and decreased quality of life in dialysis patients.